PENGAJARAN TASAWUF DALAM MENINGKATKAN KETERAMPILAN BERDAKWAH PARA SANTRI DI PONDOK PESANTREN TARBIYAH ISLAMIYAH NURUL YAQIN BATIPUAH ATEH - Ashra Ade Syukrya; Syafriwaldi Syafriwaldi (KINEMA: Jurnal Komunikasi dan Penyiaran, 2024)
The main focus of this research is to explore the methods of teaching Sufism in enhancing the preaching skills of the students and to identify the supporting and hindering factors for teachers in improving the students' preaching skills at Tarbiyah Islamiyah Nurul Yaqin Islamic Boarding School, Batipuah Ateh. The aim of this research is to describe the methods of teaching Sufism to enhance the students' preaching abilities and to identify the supporting and hindering factors for teachers in enhancing the students' preaching skills at Tarbiyah Islamiyah Nurul Yaqin Islamic Boarding School, Batipuah Ateh. The theory used in this research is the Living Qur'an. The research method employed is qualitative research with a descriptive approach, conducted naturally according to the conditions observed in the field. The data collection techniques used by the researcher include observation, interviews, and documentation. The results of this research indicate that there are three methods of teaching Sufism to enhance the students' preaching skills at Tarbiyah Islamiyah Nurul Yaqin Islamic Boarding School, Batipuah Ateh: instilling attitudes of sincerity, patience, and trust in God. The research also reveals several supporting and hindering factors for teachers in improving the students' preaching skills. The supporting factors include mastery of the material, appropriate teaching methods, a supportive environment, and evaluation and feedback. The hindering factors include the students' lack of self-confidence and limited time.